2023
DOI: 10.3390/v15030618
|View full text |Cite
|
Sign up to set email alerts
|

Surfing the Waves: Differences in Hospitalised COVID-19 Patients across 4 Variant Waves in a Belgian University Hospital

Abstract: The unprecedented COVID-19 pandemic took the form of successive variant waves, spreading across the globe. We wanted to investigate any shift in hospitalised patients’ profiles throughout the pandemic. For this study, we used a registry that collected data automatically from electronic patient health records. We compared clinical data and severity scores, using the National Institute of Health (NIH) severity scores, from all patients admitted for COVID-19 during four SARS-CoV-2 variant waves. Our study conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…During our study period, the Alpha variant was most prevalent over the largest part of the first half of 2021, while the Delta variant was dominant in the second half of the year. Although the Beta and Gamma variants were concomitantly identified over the first half of 2021, they did not play an important role in subsequent waves of SARS-CoV-2 variants observed in Belgium [ 30 , 49 ]. Furthermore, previous studies have shown that both the Alpha and Delta variants have 50%-70% higher transmissibility compared to the pre-existing variants, and they impacted individuals with similar demographic and comorbidity characteristics [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…During our study period, the Alpha variant was most prevalent over the largest part of the first half of 2021, while the Delta variant was dominant in the second half of the year. Although the Beta and Gamma variants were concomitantly identified over the first half of 2021, they did not play an important role in subsequent waves of SARS-CoV-2 variants observed in Belgium [ 30 , 49 ]. Furthermore, previous studies have shown that both the Alpha and Delta variants have 50%-70% higher transmissibility compared to the pre-existing variants, and they impacted individuals with similar demographic and comorbidity characteristics [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that the clinical characteristics of hospitalised patients with COVID-19 changed profoundly from one epidemic wave to the next but they do not analyse sociodemographic factors. 13 Meurisse et al, have also shown that more deprived municipalities were predicted to experience a higher COVID-19 incidence but this pattern of municipality-level socioeconomic inequalities was dependent on the period during the COVID-19 crisis. 14 Our study therefore focused on two Brussels university hospitals, CHU St Pierre and Érasme, located in the most deprived area of Brussels (for the former) and in a deprived area (for the latter).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
“…However, this profile is comparable to the all-cause mortality gradient in non-pandemic times. Another study has shown that the clinical characteristics of hospitalised patients with COVID-19 changed profoundly from one epidemic wave to the next but they do not analyse sociodemographic factors 13. Meurisse et al , have also shown that more deprived municipalities were predicted to experience a higher COVID-19 incidence but this pattern of municipality-level socioeconomic inequalities was dependent on the period during the COVID-19 crisis 14…”
Section: Introductionmentioning
confidence: 99%
“…Available reports have documented a milder COVID-19 course caused by the Omicron variant, lower frequency of hospitalizations and admissions to intensive care units, as well as a decrease in the mortality rate compared to previous pandemic waves [ 16 , 17 , 18 ]. However, there is a need for studies assessing the clinical diversity of cases and effects of SARS-CoV-2 during the dominance of Omicron, which is responsible for the longest wave of the pandemic.…”
Section: Introductionmentioning
confidence: 99%